Incorporating Visual Intelligence in Line Following Robots - Pujara, Dhyanik; Naik, Palak; Gautam, Riya; Mecwan, Akash (2023 IEEE International Symposium on Smart Electronic Systems (iSES), 2023)
Line follower robot is a mobile robot that is programmed to detect the path and trace the same. A colored line follower is an improved version of the line follower robot which is able to select the desired line among different colored lines as per the instructions given by the user. Line-following robots have gained significant attention due to their applications in various fields, including industrial automation, transportation, and entertainment. Traditional line-followers use basic infrared sensor-based systems, which restrict their ability to handle complex and dynamic surroundings and also work for either black or white path. In order to improve the robot's ability to navigate and track a colored path, this paper suggests two methods that make use of sophisticated image processing and computer vision algorithms. Open CV and python are used to design the path detection system and a feedback-based control loop mechanism called PID controller is also implemented for robot movement. Out of the two proposed methods, the experimental results demonstrate the effectiveness of IR Analogy Algorithm over Image Warping based algorithm.